Undang-undang 13 Tahun 1998 tentang Kesejahteraan Sosial Lanjut Usia : Stagnasi atau Revisi - Akbar, Muhammad; Nulhaqim, Soni Akhmad; Deliarnoor, Nandang Alamsah; Resnawaty, Risna (Social and Political Science Faculty - Universitas Tidar, 2023)
Indonesia is undergoing a period of demographic aging. In the fifty years after 1971, the proportion of the elderly population has climbed by 6.2% to 10.7% of the overall population of Indonesia in 2020. This proportion is expected to rise to 9.2% or 19.9% of Indonesia's overall population in the following 25 years (2045). The Indonesian people's life expectancy has likewise increased. Men have a life expectancy of 69.67 years, while women have a life expectancy of 73.55 years. One of the numerous elements influencing Indonesians' life expectancy is the quality and quantity of development in terms of social protection, health, education, and the economy. However, the growing number of elderly people is accompanied by social difficulties such as neglect, economic/social exploitation, acts of violence, maltreatment, and dealing with the law, resulting in gaps in intergenerational interactions. This can occur in both the smallest environments, such as the family, and in society as a whole. The major legislation, notably Law No. 13 of 1998 on Social Welfare of the senior, has not yet been amended to balance the development of diverse senior concerns. This modification is critical and urgent, especially given that pandemic conditions have made the elderly one of the most vulnerable groups. Reexamination of old-age categories, rights and obligations of the elderly, and the notion of service to the elderly. The role and participation of the central, province, and district/city governments, the commercial sector, academics, the family, community, media, and local groups must therefore be expanded and updated. The National Elderly Commission's independence and strengthening are other issues that require more attention. This is to adapt to society's increasingly complicated problems and advancements in the digital era, in which the old have equal access to knowledge and technology. This research technique makes use of journal literature, rules and regulations, and the author's activities as a gerontology social worker. The draft amendment of the law on old welfare is supposed to serve as a catalyst for providing optimal protection for the aged, who are projected to become healthier, more independent, and productive.